Ebstein's anomaly of tricuspid valve with aortic stenosis and coarctation of aorta: Successful single‐stage repair of a rare adult congenital heart disease. Issue 11 (16th September 2020) - Mishra, Anand Kumar; Barwad, Parag; Bansal, Vidur; Mandal, Banashree; Srivastava, Ayush; Naganur, Sanjeev Hanumantacharya
Abstract: Ebstein's anomaly of the tricuspid valve is infrequently associated with left heart anomalies. The association of aortic stenosis in Ebstein's anomaly has been reported to be extremely rare and the association of coarctation of aorta is even rarer especially in adults. The combination of all three of these lesions is virtually unknown without any references in literature. We report here an unusual case of Ebstein's anomaly of the tricuspid valve and severe aortic stenosis with coarctation of aorta in an adult who presented to us with exertional dyspnoea in the third decade and underwent a successful single‐stage intracardiac repair.